Kajian Sifat Fisik Beton Dengan Additive Natrium Tripolyphosphate Pada Pengecoran Beton Dalam Air Gambut - Wahyu Muhammad Firdaus; Ismeddiyanto Ismeddiyanto; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Under-Water Concrete (UWC) is one of the types of high-performance concrete because the mixture and the casting process are different from concrete in general. UWC casting does not allow the compaction process to be carried out in the water so by adding Admixtures Washout Agent (AWA) into concrete, the concrete's viscosity is increased and its resistance to washout is enhanced. Sodium Tripolyphosphate (STPP) is one of the additives used in this research which has AWA properties so that when casting is carried out the concrete mixture is not mixed with peat water. The use of a Superplasticizer ensures enough concrete fluidity to spread readily in place without vibration and the use of stone ash functions as a filler for the pores in the concrete. UWC must achieve the right balance between its physical and mechanical properties which can affect its performance. UWC composition and physical properties determine concrete resistance to mass loss by washout of peat water. The research aims to study the effect of STPP additive in the composition of concrete mixtures in the peat water environment and analyze UWC physical properties, i.e., workability, Fourier Transform Infra-Red (FTIR), and porosity. The amount of STPP used in this study is 10% of cement's weight while the amount of stone ash used is 10% of the fine aggregate weight. Porosity and volume weight tests were carried out on six samples, and FT-IR testing was carried out on two samples of the concrete cylinders with volumes of 10 cm diameter and 20 cm height. The parameter considered in this study was comparing the physical properties of UWC of the curing time in peat water for 28 days and 56 days. The test results of the volume weight test on 28 and 56 curing days were 2262.271 kg/m3 and 2271.331 kg/m3. The porosity test value in concrete with 28 days was 20.847% decreased by 0.165% against the concrete age of 56 days, which equals to 20.024%. It can be concluded that there was no effect of peat water at 56 days on concrete's physical properties. Key words: Natrium Tripolyphosphate, Underwater Concrete, Admixture Washout Agent, Porosity